Inferring experimental procedures from text-based representations of chemical reactions - Alain C. Vaucher (Nature Portfolio, 2021)
In organic chemistry, synthetic routes for new molecules are often specified in terms of reacting molecules only. The current work reports an artificial intelligence model to predict the full sequence of experimental operations for an arbitrary chemical equation.